Parental Responsibility and Health Lifestyle Behaviors among Young Mothers Who are Breast Cancer Survivors in China: A Structural Equation Modeling Study - Fei , Wang; Abdullah , Haslinda; Zaremohzzabieh , Zeinab; Li, Yukun; Hongjuan, Zhang (Journal of Ecohumanism, 2024)
This study aims to identify the role of parental responsibility as a central driver of health lifestyle behaviors among young mothers who are breast cancer survivors in China. The study also explores the mediating role of attitude and intention and the moderating effect of organizational culture. A cross-sectional survey of 399 young mothers who are breast cancer survivors aged 18–40 years was conducted in Liaoning, China. Data were collected using structured questionnaires. SEM was employed to analyze the relationships among constructs. The results indicate that parental responsibility significantly influences behavior through its effects on attitude (β = 0.156, p < 0.001) and intention (β = 0.142, p = 0.009), with a substantial indirect impact on behavior via attitude and intention (VAF = 47.13%). perceived benefits positively influence attitude (β = 0.144, p = 0.001) and intention (β = 0.023, p = 0.012). Organizational culture was found to moderate the relationship between parental responsibility and behavior. The findings have important implications for the development of culturally sensitive health interventions tailored to young breast cancer survivors. Practical interventions are suggested to assist young breast cancer survivors in enhancing their health behaviors by integrating parental responsibility into health promotion strategies. This study emphasizes how health behaviors can be managed more effectively within the specific cultural context of China. The findings extend the literature on health behavior by integrating parental responsibility into the health behavioral model and theory of reasoned action, offering a framework that enhances the understanding of how culturally relevant factors influence health behaviors among young breast cancer survivors a non-Western context.